PENGARUH KOMUNIKASI PEMERINTAHAN TERHADAP EFEKTIVITAS PELAKSANAAN PROGRAM ALOKASI DANA DESA DI DESA PALOAN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Rian Rinaldo E.42009050 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
This Research is intended to prove the theory that generated the experts with regard to the influence of government communication on the effectiveness of the program implementation of village fund allocations in the Paloan Village, District Sengah Temila, Landak Regency. This study was conducted departed from social phenomena regarding the effectiveness of the implementation of the program village fund allocation in Paloan Village, District Sengah Temila, Landak Regency. Government communications is considered as one of the factors that influence the effectiveness of the implementation program of village fund allocation in Desa Paloan. This study uses quantitative research methods. From questionnaires distributed, the data obtained are then processed using a computer program Statistical Product and Service Solutions (SPSS) V.18 to test the hypothesis. The subjects were Paloan villagers who had received the direct impact of the allocation of program funds in the village in the Paloan Village, District Sengah Temila, Landak Regency as many as 92 people. Results of this study is that there is a positive and significant effect of the government communication on the effectiveness of the implementation program of village fund allocations in Paloan Village, District Sengah Temila, Landak Regency. This is evidenced by the positive value of the correlation coefficient is equal to 0.314. In addition, the influence exerted of government communication to on the Effectiveness of the Program Implementation of Village Fund Allocation In the Paloan Village, District Sengah Temila, Landak Regency by 9.7%, while 90.3% is influenced by other factors outside the study. Keywords: Coordination, Cross-Sectoral, Tourism Development